Structure-guided manipulation of the regioselectivity of the cyclosporine A hydroxylase CYP-sb21 from Sebekia benihana - Fengwei Li; Li Ma; Xingwang Zhang; Jingfei Chen; Feifei Qi; Yinyue Huang; Zepeng Qu; Lishan Yao; Wei Zhang; Eung-Soo Kim; Shengying Li (Synthetic and Systems Biotechnology, 2020)
The cytochrome P450 enzyme CYP-sb21 from the rare actinomycete Sebekia benihana is capable of hydroxylating the immunosuppressive drug molecule cyclosporine A (CsA) primarily at the 4th N-methyl leucine (MeLeu4), giving rise to γ-hydroxy-N-methyl-l-Leu4-CsA (CsA-4-OH). This oxidative modification of CsA leads to dramatically reduced immunosuppressive activity while retaining the hair growth-promoting side-effect, thus demonstrating great application potential in both pharmaceutical and cosmetic industries. However, this P450 enzyme also hydroxylates CsA at the unwanted position of the 9th N-methyl leucine (MeLeu9), indicating that the regioselectivity needs to be improved for the development of CsA-4-OH into a commercial hair growth stimulator. Herein, we report the crystal structure of CYP-sb21 in its substrate-free form at 1.85 Å. Together with sequence and 3D structure comparisons, Autodock-based substrate docking, molecular dynamics (MD) simulation, and site-directed mutagenesis, we identified a number of key residues including R294, E264, and M179 that can improve catalytic efficiency or change the regioselectivity of CYP-sb21 towards CsA, setting the stage for better enzymatic preparation of CsA-4-OH. This study also provides new insights into the substrate recognition and binding mechanism of P450 enzymes that accommodate bulky substrates.